Vav proteins are key regulators of Card9 signaling for innate antifungal immunity - Roth, Susanne; Bergmann, Hanna; Jaeger, Martin; Yeroslaviz, Assa; Neumann, Konstantin; Koenig, Paul-Albert; Prazeres da Costa, Clarissa; Vanes, Lesley; Kumar, Vinod; Johnson, Melissa; Menacho-Márquez, Mauricio; Habermann, Bianca; et al. (Cell reports, 2016)
Fungal infections are major causes of morbidity and mortality, especially in immunocompromised individuals. The innate immune system senses fungal pathogens through Syk-coupled C-type lectin receptors (CLRs), which signal through the conserved immune adaptor Card9. Although Card9 is essential for antifungal defense, the mechanisms that couple CLR-proximal events to Card9 control are not well defined. Here, we identify Vav proteins as key activators of the Card9 pathway. Vav1, Vav2, and Vav3 cooperate downstream of Dectin-1, Dectin-2, and Mincle to engage Card9 for NF-κB control and proinflammatory gene transcription. Although Vav family members show functional redundancy, Vav1/2/3−/− mice phenocopy Card9−/− animals with extreme susceptibility to fungi. In this context, Vav3 is the single most important Vav in mice, and a polymorphism in human VAV3 is associated with susceptibility to candidemia in patients. Our results reveal a molecular mechanism for CLR-mediated Card9 regulation that controls innate immunity to fungal infections.